Fizikalne in mehanske lastnosti svežega in osušenega lesa v bukovih deblih, izruvanih med žledolomom - Gorišek, Željko (Acta silvae et ligni, 2017)
Physical and mechanical properties of beech wood (Fagus sylvatica L.) from trees fallen in ice storm were determined. The properties were studied in parallel green and dried beech-wood samples, systematically collected along the radius and at different height levels of the stem. The stiffness of the timber was comparatively tested with static 4-point bending and non-destructively by measuring the speed of ultrasound, and by determining the frequency response. The bending and shear strengths were additionally determined along the grain, as well as compression strength in all anatomical directions of wood. In blown down trees with still partly preserved root system, active crown and sufficient capillary water flow, we could not detect any reduction of mechanical properties due to deterioration. The density and mechanical properties, except transverse compression strength, increased with increasing height in the tree and radially from the pith to the cambium. They were always better in dried than in green wood. The reliability of non-destructive methods was greater in the evaluation of dried wood. We recommend visual wood characterisation in addition to the use of non-destructive methods for strength assessment of wood.
Keywords: bukev; Fagus sylvatica; beech wood; gostota; density; mechanical properties; mehanske lastnosti; nedestruktivno testiranje; non-destructive testing; žledolom; ice storm